2015
DOI: 10.1037/xhp0000100
|View full text |Cite
|
Sign up to set email alerts
|

The attentional cost of receiving a cell phone notification.

Abstract: It is well documented that interacting with a mobile phone is associated with poorer performance on concurrently performed tasks because limited attentional resources must be shared between tasks. However, mobile phones generate auditory or tactile notifications to alert users of incoming calls and messages. Although these notifications are generally short in duration, they can prompt task-irrelevant thoughts, or mind wandering, which has been shown to damage task performance. We found that cellular phone noti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
158
4
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(192 citation statements)
references
References 20 publications
16
158
4
2
Order By: Relevance
“…This confirms a long history of findings that notifications interrupt [4,18,33] and have negative effects on task performance [1,4,10,11,16,18,21,23,27,30,39,38]. This strengthens the need for research about delivering notifications at opportune moments [16,29,30].…”
Section: Notifications Drive Phone Use and Distractsupporting
confidence: 68%
See 1 more Smart Citation
“…This confirms a long history of findings that notifications interrupt [4,18,33] and have negative effects on task performance [1,4,10,11,16,18,21,23,27,30,39,38]. This strengthens the need for research about delivering notifications at opportune moments [16,29,30].…”
Section: Notifications Drive Phone Use and Distractsupporting
confidence: 68%
“…Since people usually attend to notifications within minutes, notifications may sometimes interrupt those other tasks. Such interruptions can have negative effects: previous work in the context of information workers has found that notifications negatively affect work efficiency when delivered in the middle of a work task [1,11,16,18,23,36,38], and the effect is more pronounced when the task is cognitively demanding [10,26]. As found by Stothart et al [38], this is even true when the notification is not attended, as tested in a controlled exam setting.…”
Section: Related Worksupporting
confidence: 54%
“…The same limitations of awareness undoubtedly underlie interactions with information technology (Levin & Baker, 2015;Varakin et al, 2004), effects of distracted driving (McCarley et al, 2004;Strayer et al, 2003), and other forms of distraction (Eriksen & Johnson, 1964;Stothart et al, 2015).…”
Section: Empirical Observationsmentioning
confidence: 99%
“…Simply knowing that a text or an e-mail, for example, has been received can lead to a user's mind wandering. 6 These addictive behaviors and constant flow of information, as well as unclear boundaries regarding the use of smartphones in health care settings, are raising very serious concerns.…”
Section: Distraction From Smartphonesmentioning
confidence: 99%